Interview Lauro Frederico Barbosa da Silveira. - Silveira, Lauro Frederico Barbosa da [UNESP]; Alves, Marcos Antonio [UNESP] (FapUNIFESP (SciELO), 2025)
The interview conducted in 2017 with Professor Lauro Frederico Barbosa da Silveira is published. This republication is a posthumous tribute to this philosopher who was one of the founders of the Trans/ Form/Ação Journal 50 years ago. A profound expert on various topics in Philosophy and other areas, Lauro was a pioneer in Semiotics studies in Brazil, having contributed to the consolidation and dissemination of the field. The interview addresses several subjects, such as the origin, academic and professional background of the interviewee, the role of semiotics, the philosopher and philosophy in the world, the inseparability between theory and practice, the Brazilian political scenario, the role of information and the media in the formation of habits, autonomous action, and the function of emotions in the production of theories.
EntrEvista com Lauro FrEdErico BarBosa da siLvEira
Keywords: Information; Philosophy; Semiotics; Sign